132k views
5 votes
Rearrange the equation to make g the subject.

SHOW ALL WORKING OUT!


f+4(g-h)=x

User Rob Deary
by
4.8k points

2 Answers

2 votes

Answer:

g=((x-f)/4)+h

Explanation:

f+4(g-h)=x

4(g-h)=x-f

g-h=(x-f)/4

g=((x-f)/4)+h

User Xiv
by
5.4k points
3 votes

Answer:

The answer is


g = (x - f)/(4) + h

Explanation:

f + 4(g - h) = x

Send f to the right side of the equation

That's

4(g - h) = x - f

Divide both sides by 4

That's

g - h = (x - f)/ 4

Send h to the right side of the equation

We have the final answer as

g = (x - f) / 4 + h

Hope this helps you

User Webmat
by
5.0k points